Reasoning with Rough Sets Logical Approaches to Granularity-Based Framework - Akama, Seiki; Murai, Tetsuya; Kudo, Yasuo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores reasoning with rough sets by developing a granularity-based framework. It begins with a brief description of rough set theory. Next, we examine some relations between rough set theory and non-classical logics including modal logic. We also develop a granularity-based framework for reasoning in which various types of reasoning can be formalized. This book will be of interest to researchers working on the areas in Artificial Intelligence, database and logic.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence